SPECIES DIVERSITY OF FOREST-STEPPE FLORA OF AKKOL DISTRICT OF AKMOLA REGION (Eurasian Journal of Ecology, 2025)
This article presents the results of studies of species diversity of floristic complex of Akkol district. This district is located in the north-eastern part of Akmola region, Republic of Kazakhstan. The studied area is characterised by forest-steppe and steppe vegetation growing mainly on chernozem soil. The research was carried out in spring and summer during field expeditions. The standard methodology of ecological profiles was used to describe plant communities. Plots of 15x15 m were laid out. Then the spectrum of plant communities characteristic for each zone was determined. Geobotanical indices were determined at each site. The Drude scale was used to estimate abundance. The inventory revealed that the flora of the forest-steppe complex is represented by 138 species belonging to 87 genera and 30 families. There are 120 species of dicotyledonous plants, which is 87 %, and 18 species of monocotyledonous plants, which is 13 % of the total species diversity. The ratio of monocotyledons to dicotyledons is 1:6.6. Most genera in this floristic complex are represented by one species, respectively the average value is 1.5. The autochthonous tendency of flora formation in Akkol district of Akmola region is confirmed by the complete absence of endemic species in the studied area.Keywords: species diversity, steppe flora, forest flora, floristic complex, taxonomic composition